Control of fatty acid distribution in phosphatidylcholine of spinach leaves - K.A. DEVOR; J.B. MUDD (Journal of Lipid Research, 1971)
The acylation of lysophosphatidylcholine by enzyme preparations from spinach leaves was studied. The acylation reaction was followed by the incorporation of 14C-labeled fatty acids from the respective coenzyme A derivatives into phosphatidylcholine. The subcellular fraction with the highest specific activity was the microsomal fraction. Contaminating thioesterase activity which was encountered was inhibited by treatment with sodium dodecyl sulfate. The acyltransferase activity was only mildly inhibited by sulfhydryl reagents. Labeled fatty acid was primarily incorporated into phosphatidylcholine. When saturated and unsaturated fatty acyl CoA derivatives were used, the saturated derivatives were incorporated primarily into the 1-position of the glycerol moiety, and the unsaturated fatty acids went primarily to the 2-position. This pattern of incorporation agrees with the fatty acid distribution in vivo.